Dosimetric Comparison of the Linear Accelerators at the University Hospital of Radiotherapy and Oncology in Skopje, Macedonia - Nikolovski, Dragan; Lukarski, Dushko (Association for Medical Physics and Biomedical Engineering, Skopje, Macedonia, 2013)
In radiotherapy practice, for various practical reasons it is important to know whether two or more linear accelerators (linacs) are dosimetrically matched and whether the patient’s treatment can be shifted from one linac to another without reducing the treatment quality. This work presents the data from the dosimetric comparison of the two Varian Clinacs 23EX and one Varian Clinac iX at the University Clinic of Radiotherapy and Oncology in Skopje. Both Percentage Depth Dose (PDD) and Beam Profile (BP) curves were compared for the photon energies (6MV, 15MV) in use at the clinic. The comparison was performed using the IBA OmniPro Accept 7.4™ software. The results from the comparison of the PDD curves showed that in the clinically significant region the dose differences were smaller than 1%. The results from the comparison of the inline and crossline BP curves showed that in the flattened area the dose differences were smaller than 2.5%, while in the penumbra region they were usually between 2% and 8%, but sometimes up to 21%. This suggests that for treatments where the influence of the penumbra region is small, the three linacs may be considered to be dosimetrically matched. For treatments where the influence of the penumbra region is greater, the patient can be switched to another machine only after recalculation of the treatment plan.
Keywords: Linac matching